The Sticker Collector′s Problem. (1st September 2016) - Diniz, M. A.; Lopes, D.; Polpo, A.; Salasar, L. E. B.
Summary: We present a generalization of the coupon collector′s problem called the sticker collector′s problem. We cover four different ways to handle the problem, illustrating the results with the stickers of the FIFA World Cup album. This material could be used as motivating examples in undergraduate courses.